Penerapan Moderasi Beragama di Indonesia: Harmonis dan Inklusif - My Esti Wijayati; Fuad (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
This study explores the implementation of religious moderation as a strategic step toward realizing a more harmonious and inclusive future for Indonesia. The method used in this research is the literature review method, with a descriptive analysis approach, analyzing documents related to and implemented by programs of religious moderation in Indonesia. The research results show that the challenges faced by the government in implementing religious moderation include resistance from conservative groups and a lack of support from educational institutions. This study concludes that religious moderation is a key factor in building a harmonious and inclusive Indonesia by strengthening cooperation between the government, religious leaders, and society in promoting the values of moderation. Thus, religious moderation can become a strong foundation for the sustainability of peace and social stability in Indonesia.